Effect of multistage isolation of neutrophils on their counts and viability - I. N. Shvydchenko; E. Yu. Bykovskaya; V. V. Golubtsov (Медицинская иммунология, 2025)
Despite numerous separation methods of neutrophils from peripheral blood, isolation of sufficient quantities of high-purity viable cells for quantitative determination of neutrophil cytokines and their mRNA expression still remains an actual issue. The recommended multi-step purification methods significantly prolong the cell isolation process, potentially leading to cell activation or apoptosis and resulting in significant cell loss. Preliminary purification of neutrophils is the most critical stage in terms of time spent, and several additional manipulations with cells. To address this challenge, our study aimed to compare various methods of preliminary neutrophil isolation in order to select the optimal approach to obtaining a sufficient number of viable peripheral neutrophils.We studied the effects of three different protocols for preliminary isolation of cell suspensions: (a) centrifugation of whole blood at a single-step density gradient followed by sedimentation of red blood cells with dextran; (b) centrifugation of whole blood on a double density gradient; (c) rapid isolation of leukocytes using a reagent that promotes red blood cell aggregation. The cell counts and viability of purified neutrophils were tested at the final stage using negative immunomagnetic selection. Our study has shown that the methods used for preliminary neutrophil isolation significantly affect both the number and viability of the cells. The highest number of viable neutrophils was obtained using a conventional method of blood centrifugation at a density gradient followed by dextran sedimentation of red blood cells. However, the three studied methods of preliminary neutrophil isolation did not show statistically significant differences with respect to quantitative yield of viable cells after immunomagnetic isolation. These findings suggest that any of these methods may be applied, depending on capabilities and preferences of the researchers. In summary, our findings confirm previous studies indicating that the multistep process of neutrophil isolation allows for obtaining a high-purity cell suspension (> 99.1%) which can be used in future studies of their cytokine-secreting activity. However, such multi-stage isolation significantly reduces the yield of neutrophils, thus being critical for studying of initially small blood volumes.